Answer:
![y=5](https://img.qammunity.org/2020/formulas/mathematics/high-school/vz87m1ge16cb4tz4pxuo69xmt9ogjrotw7.png)
Explanation:
we have the expression:
![-6x - 3y = 57](https://img.qammunity.org/2020/formulas/mathematics/middle-school/dvg46hyyzhdciokv6cka2gesvobdpx89l2.png)
and we are told that
, so we must substitute this value in the previous equation and then clear for the variable y:
substituting x:
![-6(-12)-3y=57](https://img.qammunity.org/2020/formulas/mathematics/middle-school/ydtig1ekkqsfrb3kccfoce5ags98i12mop.png)
clearing for y:
![72-3y=57\\-3y=57-72\\-3y=-15\\y=(-15)/(-3)\\ y=5](https://img.qammunity.org/2020/formulas/mathematics/middle-school/m569srtj143ehxq5pmzx73o7192sqafhcz.png)
and we can corroborate this result by substituting the values in the original equation
![-6(-12)-3(5)=72-15=57](https://img.qammunity.org/2020/formulas/mathematics/middle-school/typ5uwgl3kcl49mjswl8bwyo605i1ds3nm.png)